Impact of Powered Toothbrush Use and Interdental Cleaning on Oral Health - Pitchika, V. (J Dent Res, 2020)
The long-term effectiveness of powered toothbrushes (PTBs) and interdental cleaning aids (IDAs) on a population level is unproven. We evaluated to what extent changes in PTB and IDA use may explain changes in periodontitis, caries, and tooth loss over the course of 17 y using data for adults (35 to 44 y) and seniors (65 to 74 y) from 3 independent cross-sectional surveys of the German Oral Health Studies (DMS). Oaxaca decomposition analyses assessed to what extent changes in mean probing depth (PD), number of caries-free surfaces, and number of teeth between 1) DMS III and DMS V and 2) DMS IV and DMS V could be explained by changes in PTB and IDA use. Between DMS III and V, PTB (adults: 33.5%; seniors: 28.5%) and IDA use (adults: 32.5%; seniors: 41.4%) increased along with an increase in mean PD, number of caries-free surfaces, and number of teeth. Among adults, IDA use contributed toward increased number of teeth between DMS III and V as well as DMS IV and V. In general, the estimates for adults were of lower magnitude. Among seniors between DMS III and V, PTB and IDA use explained a significant amount of explained change in the number of caries-free surfaces (1.72 and 5.80 out of 8.44, respectively) and the number of teeth (0.49 and 1.25 out of 2.19, respectively). Between DMS IV and V, PTB and IDA use contributed most of the explained change in caries-free surfaces (0.85 and 1.61 out of 2.72, respectively) and the number of teeth (0.25 and 0.46 out of 0.94, respectively) among seniors. In contrast to reported results from short-term clinical studies, in the long run, both PTB and IDA use contributed to increased number of caries-free healthy surfaces and teeth in both adults and seniors.